Design of a live-attenuated bacterial vaccine using effector network engineering - Frankel,G (Nature Communications, 2026)
Enteropathogenic Escherichia coli (EPEC) and Citrobacter rodentium (CR) are extracellular enteric attaching and effacing (A/E) pathogens of humans and mice, respectively. Their virulence relies on intimate bacterial attachment and a network of type III secretion system effectors. Here, through systematic reduction and redesign of the effector network in CR, we develop an attenuated strain, CRV (CR Vaccine), encoding a subset of ten effectors. CRV colonises C57BL/6 mice ~100-fold lower than wild type CR (CRWT) without causing overt pathogenesis. Moreover, C3H/HeN mice, which succumb to CRWT infection, survive CRV challenge. Vaccination with CRV confers protection against subsequent CRWT infection in both mouse strains. Serological analysis reveals a repertoire of dominant CR antigens, including the O-antigen, the virulence factors intimin, EspA and Tir and the outer membrane proteins Lpp, OmpA, MetQ and CARC (an AIDA-like autotransporter). We show that CRWT and CRV immunisation elicits comparable B cell and antibody responses, which is contingent on intimate bacterial attachment. A corresponding EPEC strain (E. coli Vaccine, ECV) effectively colonises epithelial cells in a gut-on-chip model. These findings establish effector network minimisation as a generalisable strategy for rational bacterial attenuation and live-attenuated vaccine design.